"Passivity more passive than all passivity". Notes on a central notion in the writings of maturity of E. Levinas - Maddonni, Luciano (2017)
The article proposes some notes on the notion of passivity developed in the maturity writings of the Jewish philosopher Emmanuel Levinas, considered one of the fundamental pillars on which his complex discourse on ethical subjectivity and responsibility to substitution is based. Achieved thanks to what the author himself calls the method of emphasis, the levinasian proposal on this notion is condensed in the iterative construction: "passivity more passive than all passivity." With this figure, the philosopher seeks, on the one hand, to take the notion beyond the uses that made the philosophical tradition and, on the other hand, to reach the final phenomenological foundation of his conception of ethical subjectivity that, breaking with his ontological enclave, is conceived as being otherwise